2011
DOI: 10.1142/s0219455411004324
|View full text |Cite
|
Sign up to set email alerts
|

Postbuckling Analysis of Variable Stiffness Composite Plates Using a Finite Element-Based Perturbation Method

Abstract: Modern fiber placement machines allow laminates with spatially varying stiffness properties to be manufactured. In earlier research, the authors optimized variable stiffness plates for maximum buckling load, demonstrating significant improvements in load-carrying capacity. In aerospace applications, panel structures are often permitted to enter the postbuckling regime during service. It is, therefore, not only important to understand their postbuckling behavior, but also to develop fast analysis methods that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…In the past several years, drastic improvements in the manufacturing techniques allowed variable-stiffness constructions to become a hot topic and suitable candidates for the aerostructures of the next generation. Theoretical investigations and numerical models were carried out for analyzing their buckling [19][20][21] and post-buckling [22][23][24] response, in most cases referring to thin plate theory or FSDT [25]. Refined theories have been less commonly employed: the free vibration response of variable-stiffness plates (VSP) is investigated in [26,27] using finite elements, while the authors presented a variable-kinematics, Ritz-based procedure for buckling and free-vibration analysis [28] of VSP based on Carrera's Unified Formulation (CUF) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, drastic improvements in the manufacturing techniques allowed variable-stiffness constructions to become a hot topic and suitable candidates for the aerostructures of the next generation. Theoretical investigations and numerical models were carried out for analyzing their buckling [19][20][21] and post-buckling [22][23][24] response, in most cases referring to thin plate theory or FSDT [25]. Refined theories have been less commonly employed: the free vibration response of variable-stiffness plates (VSP) is investigated in [26,27] using finite elements, while the authors presented a variable-kinematics, Ritz-based procedure for buckling and free-vibration analysis [28] of VSP based on Carrera's Unified Formulation (CUF) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works on variable stiffness laminates focused mainly on initial buckling and report an increase in critical buckling load by re-distribution of the prebuckling stresses Wu et al, 2012c). However, very few works (Rahman et al, 2011) have been reported on the study of postbuckling behaviour of VAT laminates, and where they exist, rely substantially on finite element modelling, which requires significant computational efforts in solving the nonlinear postbuckling problem. There remains an ongoing need for rapid design tools which allow optimisation studies and provide physical insight into the fundamental behaviour which is not always readily achievable using commercial finite element analysis (FEA).…”
Section: Introductionmentioning
confidence: 99%
“…The numerical perturbation approach to postbuckling analysis should be mentioned as rather popular. For references, one may refer to [3], [8], and [15].…”
mentioning
confidence: 99%